Growth and differentiation factor 15 (GDF15) levels predict adverse respiratory outcomes in premature neonates. Issue 1 (14th October 2022) - Almudares, Faeq; Hagan, Joseph; Chen, Xinpu; Devaraj, Sridevi; Moorthy, Bhagavatula; Lingappan, Krithika
Abstract: Growth and differentiation factor 15 (GDF15) is a stress‐responsive cytokine, and its expression increases during inflammation, hyperoxia, and senescence. Significantly, GDF15 is secreted by the placenta, and maternal levels increase throughout pregnancy. Serum GDF15 level is a promising biomarker for many lung diseases like pulmonary hypertension and pulmonary fibrosis. However, circulating GDF15 levels in preterm infants and their role as a predictor of respiratory outcomes have not been studied. We hypothesized that GDF15 levels would increase with gestational age at birth, and that postnatal GDF15 will be correlated with adverse respiratory outcomes in preterm infants. Scavenged blood samples were retrieved from 57 preterm infants at five time points, from birth until 36‐weeks postmenstrual age (PMA). GDF15 levels were measured using ELISA in 114 samples. We performed two‐sample t ‐test, correlation and linear regression, logistic regression, and mixed‐effects linear models for statistical analysis, and significance was identified when p  < 0.05. Contrary to our hypothesis, for every 1‐week increase in gestational age at birth, the predicted GDF15 level decreased by 475.0 pg/ml ( p  < 0.001). Greater PMA was significantly associated with lower serum GDF15 levels ( p  < 0.001). Interestingly, higher GDF15 levels were associated with a longer need for mechanical ventilation ( p  = 0.034), prolonged respiratory support need ( p  < 0.001), and length of hospital stay ( p  = 0.006). In conclusion, in preterm infants, GDF15 levels show an inverse correlation with gestational age at birth, with higher levels in more preterm babies, and levels trend down postnatally. Furthermore, longitudinal GDF15 levels through 36 weeks PMA predict adverse respiratory outcomes in preterm infants.